2006
DOI: 10.1158/1078-0432.ccr-05-2729
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytosine Deaminase Fusion Gene Enhances the Effect of Radiation on Breast Cancer in Bone by Reducing Tumor Burden, Osteolysis, and Skeletal Fracture

Abstract: Background: Painful breast carcinoma metastases in bone are a common manifestation of malignant disease. Eradication of these tumors can be evasive, and as a result, skeletal morbidity increases with disease progression. Experimental Design: The treatment potential of cytosine deaminase (CD) gene therapy combined with radiation treatment was evaluated in vitro and in vivo using a 4T1 murine breast carcinoma model. 4T1 carcinoma cells were transduced with a fusion gene encoding the extracellular and transmembra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…Trastuzumab, a monoclonal antibody directed against HER2/neu oncogene, has been shown to inhibit skeletal metastases in breast cancer [120], but trastuzumab has also been associated with cardiac dysfunction, congestive heart failure, and pulmonary toxicity [121]. New agents are being developed to treat skeletal metastases (Table 2) [122][123][124][125][126][127][128][129][130][131], but they also have some safety and specificity drawbacks. Receptor activator of nuclear factor-κB ligand (RANKL) mediates osteoclast differentiation and is found to be elevated in breast cancer cells causing excessive bone resorption.…”
Section: Skeletal Metastases In Breast Cancer: Unmet Needsmentioning
confidence: 99%
“…Trastuzumab, a monoclonal antibody directed against HER2/neu oncogene, has been shown to inhibit skeletal metastases in breast cancer [120], but trastuzumab has also been associated with cardiac dysfunction, congestive heart failure, and pulmonary toxicity [121]. New agents are being developed to treat skeletal metastases (Table 2) [122][123][124][125][126][127][128][129][130][131], but they also have some safety and specificity drawbacks. Receptor activator of nuclear factor-κB ligand (RANKL) mediates osteoclast differentiation and is found to be elevated in breast cancer cells causing excessive bone resorption.…”
Section: Skeletal Metastases In Breast Cancer: Unmet Needsmentioning
confidence: 99%
“…5-FC treatment of Tg/NCD mice caused a profound reduction in the capacity of bone marrow cells collected 4 and 7 days after 5-FC treatment to form osteoclasts in vitro, but did not have a significant effect on osteoclast number. This apparent paradox of effects on osteoclast precursors but not on mature osteoclasts most likely reflects the fact that osteoclast precursor cells are engaged in cell division and thus more sensitive to 5-FU, whereas the mature osteoclasts are quiescent and less sensitive to 5-FU (24).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-activated promoters could also be considered as bone cancer is commonly treated with radiation, and 5-FU can function as a radiation enhancer (34)(35)(36). In fact, recent work describes the CD/5-FC enzyme/prodrug system as capable of enhancing the killing effect of radiation on breast cancer tumors in bone (24,36).…”
Section: Discussionmentioning
confidence: 99%
“…176 When sarcoma cells (10 5 in 20 μl) were implanted into mouse femurs to examine the effects of 20-Gy and 30-Gy radiation as a means to control cancer pain, these radiation therapies effectively decreased cancer-induced osteolysis, reduced tumor size by 75%, and decreased bone cancerrelated pain. [57][58][59] Radiation therapy also successfully controlled pain and skeletal fractures associated with femoral implantation of 4T1 breast carcinoma cells into mice. 59 These studies demonstrated that radiation therapy effectively decreased cancer-induced pain by direct effects on tumor cells.…”
Section: Models Of Cancer Painmentioning
confidence: 99%
“…[57][58][59] Radiation therapy also successfully controlled pain and skeletal fractures associated with femoral implantation of 4T1 breast carcinoma cells into mice. 59 These studies demonstrated that radiation therapy effectively decreased cancer-induced pain by direct effects on tumor cells. 57,58 Support for the effects of radiation therapy also comes from studies in which transplantable hepatocellular carcinoma cells, HCa-1, were injected into the periosteal membrane of the foot dorsum in C3H/ HeJ mice.…”
Section: Models Of Cancer Painmentioning
confidence: 99%